Study of fibrinogen levels in patients of acute stroke - Khandait, Vinod; Barai, Pratik (International Journal of Research in Medical Sciences, 2018)
Background: Stroke is a disease of paramount public health significance. The role of plasma fibrinogen in determining incidence and severity of stroke has been postulated time and again. Present study was undertaken to determine the correlation between mean plasma fibrinogen level and infarct volume on CT scan in patients with acute stroke. Methods: Present prospective observational study of two years duration at our tertiary care government centre entailed enrollment and radiological assessment (CT scan/MRI) of 50 consecutive patients with first-ever stroke admitted within 24 h after stroke onset along with measurement of their plasma fibrinogen levels at admission. Results: Thirty (60%) cases reported ischemic stroke while haemorrhagic stroke was observed in 20 (40%) cases. The mean fibrinogen levels in ischemic (584±62mg/dl) and haemorrhagic stroke (52±28mg/dl) were found to be significantly higher (p<0.05) than normal range of (200-400mg/dl). The mean infarct volume in patients with ischemic stroke was 62.79±9.51cm3 while mean plasma fibrinogen level was 584±62mg/dl. There was significant correlation between infarct volume and fibrinogen levels (r coefficient =0.61; p<0.05). The fibrinogen levels in patients who died was insignificantly higher as compared to patients who survived. Conclusions: We report significantly higher than normal mean fibrinogen levels in ischemic and haemorrhagic stroke with the correlation between infarct volume and fibrinogen levels being significant in ischemic stroke. Limited mortality numbers probably didn’t allow the present study to reach the level of significance. Similar studies with larger sample size are recommended.